Optimising IBD patient selection for de-escalation of anti-TNF therapy to immunomodulator maintenance. Issue 1 (3rd May 2019) - Swann, Rachael; Boal, Alan; Squires, Seth Ian; Lamb, Carly; Clark, Laura Louise; Lamont, Selina; Naismith, Graham
Abstract : Objective: Inflammatory bowel disease (IBD) is increasingly managed with the use of biologic therapies. National guidelines (National Institute for Health and Care Excellence (NICE)) suggest considering cessation after 1 year of therapy but lack detailed criteria for this. We aimed to describe clinical outcomes from the introduction of a biologic review panel (BRP) to implement modified criteria for cessation of antitumour necrosis factor (anti-TNF) therapy and step down to single-agent immunomodulator. Design: Retrospective review of patient outcomes following BRP implementation. Patients: All patients on biologic therapy discussed in the BRP within a 5-year period. Setting: Single IBD network covering three hospital sites. Interventions: Modified criteria for biologic cessation were based on published evidence; they excluded individuals with no suitable maintenance immunomodulator, previous surgery or evidence of active disease, additional indications for anti-TNF therapy and previous relapse on biologic cessation. All patients with IBD on a biologic were discussed at the BRP. Main outcome measures: Relapse following IBD cessation and relative cost of BRP. Results: 136 patients with IBD were reviewed, with 45 patients meeting the NICE guideline criteria for cessation. The BRP and modified criteria affected decision to withdraw therapy in 38% of these. Therapy was withdrawn in 27 patients, with a 20% 24-month relapse rate. Younger age at cessation was significantly associated with relapse (p=0.01). Conclusion: The BRP approach has proved a safe and effective means of decision making in stopping biologic therapy. Future work to inform exclusion criteria is required.